Rheumatoid Arthritis Is Associated With an Increased Risk of Postoperative Infection and Revision Surgery in Elderly Patients Undergoing Anterior Cervical Fusion. Issue 17 (1st September 2018) - Horowitz, Jason A.; Puvanesarajah, Varun; Jain, Amit; Li, Xudong J.; Shimer, Adam L.; Shen, Francis H.; Hassanzadeh, Hamid
Abstract : Study Design: Retrospective review. Objective: To identify the incidence and analyze the risk of postoperative complications amongst elderly patients with rheumatoid arthritis undergoing anterior cervical fusion. Summary of Background Data: Previous studies have reported elevated risks of postoperative complications for patients with rheumatoid arthritis undergoing orthopedic procedures. However, little is known about the risk of postoperative complications in rheumatoid arthritis patients after spine surgery. Methods: A commercially available database was queried for all Medicare patients 65 years of age and older undergoing one- or two-level primary anterior cervical fusion surgeries from 2005 to 2013. Complications, hospitalization costs, and length of stay were queried. Multivariate logistic regression analyses were performed to estimate the odds ratio for each complication adjusted for age, sex, and Charlson Comorbidity Index. Results: A total of 6067 patients with a history of rheumatoid arthritis and 113, 187 controls were identified. Significantly higher incidences of major medical complications (7.5% vs. 5.9%, P  < 0.001), postoperative infections (2.6% vs. 1.5%, P  < 0.001), and revision surgery (1.1% vs. 0.6%, P  < 0.001) were observed amongst the rheumatoid arthritis cohort. Significantly greater average cost of hospitalization ($17, 622 vs. $12, 489, P  < 0.001) and average length of stay (3.13 vs . 2.08 days, P  < 0.001) were also observed. Conclusion: Patients with rheumatoid arthritis undergoing anterior cervical fusion face increased risks of postoperative infection and revision surgery compared to normal controls. This information is valuable for preoperative counseling and risk stratification. Level of Evidence: 3